Gottfried Benn und die doppelte Staatsgründung 1949 – zu ausgewählten Prämissen seines schwierigen Verhältnisses zu Staat an sich und zum bundesdeutschen (Teil-)Staat - Walkowiak, Maciej (Studia Germanica Posnaniensia, 2017)
The paper is mainly concerned with Gottfried Benn’s complex attitude to the state and history. By means of introductory prefigurations, such as existential tensions related to the conflict between Protestant ethics and modern aesthetics, there emerges Benn’s difficult and complex relation to the state as such, seen as a product of history, and to its particular examples, starting from the Second Reich until the initial phase of West Germany. Friedrich Nietzsche’s philosophy, and in particular the philosophy of art, is of great importance in this context. This issue is discussed using Benn’s key works such as Roman des Phänotyp or Doppelleben. Benn’s literary and life self-creations played a vital role in his relations with the political reality and the state, which is discussed at the end of this analysis. His ambivalent relation to early West Germany has a strong biographical basis, i.e. his involvement with the history of the Nazi Germany on the one hand, and on the other – the period of his literary fame at the end of his life.